ANTI-EVASION PROVISIONS APPLICABLE TO VALUE-ADDED TAX IN THE REPUBLIC OF SERBIA - Vasović, Miloš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Value Added Tax (VAT) is more susceptible to tax evasion compared to other forms of taxation, primarily due to the credit-invoice mechanism and the relatively high standard rate, both of which contribute to a higher volume of evaded tax revenue.In this paper, the author examines three anti-evasion measures provided for under the legal framework of the Republic of Serbia. One such measure is the reverse charge mechanism, which requires the recipient of the supply to report and account for the tax liability, as specified on the invoice. This regime applies only to certain categories of transactions.Where the application of the reverse charge mechanism is not feasible, the tax administration may resort to two additional anti-evasion tools: the secondary tax liability (or derivative tax liability) and the principle of economic substance over form. Each of these measures has inherent limitations.Assuming that the protection of national fiscal interests is imperative, and recognizing the need for further alignment of Serbia’s VAT legislation with the acquis communautaire in this area, the author recommends amendments to the existing legal provisions aimed at enhancing the efficiency of VAT collection and reducing opportunities for tax evasion.
Keywords: tax evasion; reverse charge mechanism; joint tax liability; principle of facticity; VAT Directive 2006/112; value-added tax